The Rizal Provincial Library an evaluation of its library collection and services - Alberto, Lizbeth L. (1996)
This study is undertaken to evaluate the library collection and services of the Rizal Provincial Library. The following are the objectives of this study: 1) to find out the holdings of the library; 2) to know the extent of the collection being used by its clientele; 3) to determine whether the library collection is able to support the information, education, social, and recreation needs of its clientele; 4) to know the different services offered by the Rizal Provincial Library to its clientele; 5) to determine whether the library complies with the Minimum Standards for Public Libraries in the Philippines, and ; 6) to know the strengths and weaknesses of the library collection and services.